# Evaluate 25

Evaluate following expression:

[ 3 + ( 40 ÷ 5 ) x ( 2 x 2 ) ] – 5 =

[ 3 + ( 40 ÷ 5 ) x ( 2 x 2 ) ] – 5 =

### Correct answer:

#### You need to know the following knowledge to solve this word math problem:

## Related math problems and questions:

- Parentheses: 34731

Evaluate the expression with parentheses: 12 • (-4,3) + 3 • [14- (23-4 • 5)] - 2 • {36- [18- (28-76)]} = - Evaluate - order of ops

Evaluate the expression: 32+2[5×(24-6)]-48÷24 Pay attention to the order of operation including integers - Expression 8

Evaluate this expressions: a) 5[3 + 4(2.8 - 3)] b) 5×(8-4)÷4-2 - Expression with brackets

Evaluate the expression. 15+[(9-4)×22] - Simplify

Simplify the following problem and express as a decimal: 5.68-[5-(2.69+5.65-3.89) /0.5] - Solve equation

solve equation: [(a^{2})+3]^{1/2}+ [(a^{2})-3]^{1/2}= 5 - Fractions and mixed numerals

(a) Convert the following mixed numbers to improper fractions. i. 3 5/8 ii. 7 7/6 (b) Convert the following improper fraction to a mixed number. i. 13/4 ii. 78/5 (c) Simplify these fractions to their lowest terms. i. 36/42 ii. 27/45 2. evaluate the follow - Which 7

Which choice is NOT equivalent to the following expression? 9 x { [ 14 ÷ 2 + (4-1) ] - 8 } A 9 x { 10 - 8 } B 9 x { [ 14 ÷ 2 + 3] - 8 } C 9 x 10 - 8 D 18 - With bracket

Calculate (evaluate) simple mathematical expression with a negative numbers and a bracket: 13+15*5-2*(-6) - Expression 68414

The expression 3x - [2 - (2x - 1) + x] is given. Determine for which numbers x the expression is equal to 0. - Evaluate 19

Evaluate expression (-8-b)+6c if b=-5 and c=2 - Evaluate 26

Evaluate square root: √1³+2³+3³+4³= - Evaluate expression

Calculate the value of the expression z/3 - 2 z/9 + 1/6, for z = 2 - Consider 2

Consider the following formula: y = 3 ( x + 5 ) ( x - 2 ) Which of the following formulas is equivalent to this one? A. Y=3x²+9x-30 B. Y=x²+3x-10 C. Y=3x²+3x-10 D. Y=3x²+3x-30 - Expression

If A=2 B=3 evaluate expression A(B+A) and multiply it by A - Equations

Solve following system of equations: 6(x+7)+4(y-5)=12 2(x+y)-3(-2x+4y)=-44 - Evaluate expression

Evaluate following expression: 5 to the power of 2 - (4x4) divided by 2 =